The Management of the School Principal at the Early Childhood Education Institution of TK GMIM Pniel Bahu, Manado City - Susan Stefania Samahati; Tinneke Evie Meggy Sumual; Elni Jeini Usoh (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to describe and analyze the school principal’s management at an early childhood education institution, TK GMIM Pniel Bahu in Manado City, focusing on the four main management functions: planning, organizing, implementing, and supervising. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, participatory observation, and documentation review, and analyzed descriptively. The findings indicate that the principal manages the school effectively by integrating Christian values, a familial culture, and a participatory approach into all managerial functions. Planning is conducted collaboratively with teachers and parents; organizing involves proportional task distribution and cross-sector partnerships; program implementation reflects participatory and holistic leadership; while supervision is carried out in a reflective, transparent manner, oriented toward quality improvement. These results show that the school management not only aligns with classical management principles (POAC) but also reflects transformational, participatory, and community-based leadership. This study reinforces the crucial role of the school principal as an instructional leader who inspires and serves within a contextual and value-driven early childhood education environment.